The Impact of Managerial Ownership, Corporate Size, and Company Age on Financial Performance in Mining Firms - Paradiva, Chantica Ayu; Suryandani, Wulan (Lembaga Riset Ilmiah, 2026)
Corporate financial condition is reflected in financial performance as outcome of managerial decisions. Prior studies show inconsistent results regarding effects of managerial ownership, firm size, and company age in high-risk mining sector, creating research gap. This study examines these effects on mining companies listed on IDX during 2020–2024. Using purposive sampling, 10 companies were selected from 52 populations. Data were analyzed using multiple linear regression with classical assumption tests and t-test. Results show that managerial ownership has a positive insignificant effect, firm size has a positive significant effect, and company age has negative insignificant effect on financial performance. The model explains 33.9% of the variation in financial performance. This study contributes theoretically to literature and practically for managerial and investment decision-making. Kondisi keuangan perusahaan tercermin dari kinerja keuangan sebagai hasil dari keputusan manajerial. Penelitian sebelumnya menunjukkan hasil tidak konsisten mengenai pengaruh kepemilikan manajerial, ukuran perusahaan, dan umur perusahaan pada sektor pertambangan berisiko tinggi, sehingga terdapat research gap. Penelitian ini bertujuan menganalisis pengaruh variabel terhaap perusahaan pertambangan yang terdaftar di BEI periode 2020–2024. Dengan metode purposive sampling, diperoleh 10 perusahaan dari 52 populasi. Analisis data menggunakan regresi linier berganda dengan uji asumsi klasik dan uji t. Hasil penelitian menunjukkan kepemilikan manajerial berpengaruh positif tidak signifikan, ukuran perusahaan berpengaruh positif signifikan, serta umur perusahaan berpengaruh negatif tidak signifikan terhadap kinerja keuangan. Nilai koefisien determinasi (R²) sebesar 33,9% menunjukkan kemampuan model dalam menjelaskan variasi kinerja keuangan. Penelitian ini memberikan kontribusi teoritis dan implikasi praktis bagi manajemen dan investor dalam pengambilan keputusan.